Pengaruh Mekanisme Tata Kelola Perusahaan Terhadap Kecurangan Laporan Keuangan Dengan Koneksi Politik Sebagai Pemoderasi - Rampay, Arthur Samuel; Subekti, Imam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to determine the effect of corporate governance mechanisms, including foreign ownership, institutional ownership, and the number of sub-committees of the board of commissioners on financial statement fraud moderated by political connections. The samples include 84 manufacturing companies listed on the Indonesia Stock Exchange between 2019 and 2021 selected through purposive sampling, analyzed by multiple hierarchical regression, and processed by Statistical Product and Service Solution (SPSS) version 26 software. The results exhibit that the number of sub-committees of the board of commissioners has a negative effect on financial statement fraud while foreign ownership has a positive effect on financial statement fraud. Furthermore, political connections strengthen the positive relationship between institutional ownership and financial statement fraud. The other result of this study finds that the political connection that moderates the relationship between foreign ownership and the number of sub-committees of the board of commissioners has no effect on financial statement fraud.